Effect of LGBT anti-discrimination laws on school climate and outcomes for lesbian, gay, and bisexual high school students - Fields, Xavier; Wotipka, Christine Min (Journal of LGBT youth, 2022)
Lesbian, gay, bisexual, and transgender (LGBT) high school students face challenges that impede their academic, social, and emotional well-being. School policies that provide resources and protections for LGBT students mitigate these challenges and lead to better outcomes for LGBT students. At the same time, LGBT individuals face challenges in sectors like employment protection and hate crime prevalence, and many states have passed laws that expand protections for these adults. This paper aims to investigate the relationship between state-level, LGBT anti-discrimination policies, and high school student well-being by analyzing patterns of policy diffusion and the policies' effects on four measures of students' well-being: self-reported (1) experiences with bullying at school, (2) cyberbullying, (3) school absences due to feeling unsafe at school, and (4) grades. Using data from the Center for Disease Control's Youth Risk Behavior Surveillance System and linear regression analysis with time and state fixed effects, the results of this analysis provide evidence on the benefits of expansive civil rights legislation for LGBT individuals and the spread of its externalities to students in the U.S. schools.